Resin composition and molded article

A triester compound enhances polycarbonate resin compositions by improving surface hardness, transparency, and abrasion resistance, addressing nail scratches and solvent wipe resistance in painted-less applications.

JP7621051B2Active Publication Date: 2025-01-24MITSUBISHI CHEM CORP
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2018194538
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2018-10-15
Publication Date
2025-01-24
Estimated Expiration
2038-10-15

AI Technical Summary

Technical Problem

Polycarbonate resin compositions face issues with nail scratches and reduced transparency when used in painted-less applications, despite having high pencil hardness, and existing additives do not consistently provide adequate abrasion resistance and solvent wipe resistance.

Method used

Incorporating a triester compound derived from a polyhydric alcohol with 20 or more carbon atoms and a polyvalent carboxylic acid into the polycarbonate resin, with specific structural units, to enhance surface hardness, transparency, and abrasion resistance.

Benefits of technology

The resin composition achieves high surface hardness, excellent transparency, and improved nail scratch resistance both initially and after solvent wiping, with low haze and effective extrusion properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007621051000001
    Figure 0007621051000001
  • Figure 0007621051000002
    Figure 0007621051000002
  • Figure 0007621051000003
    Figure 0007621051000003
Patent Text Reader

Abstract

To provide a resin composition having high surface hardness, excellent extrusion properties, high transparency, and excellent resistance to nail damage in the initial stage and after solvent wiping, and a molding including the resin composition.SOLUTION: The resin composition contains, based on 100 pts.mass of a (A) polycarbonate resin, 0.3-10.0 pts.mass of a (B) triester compound. The (A) polycarbonate resin contains 5 mol% or more of a structural unit represented by the following formula. The (B) triester compound is an ester compound obtained from a polycarboxylic acid and a monohydric alcohol having 20 or more carbon atoms, an ester compound obtained from a polyhydric alcohol and a monovalent carboxylic acid having 20 or more carbon atoms, or a mixture of them. In the following formula, Ris a methyl group, Ris a hydrogen atom or a methyl group, Xis a predetermined group.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a resin composition and a molded article, and more particularly to a resin composition using a polycarbonate resin that can provide a molded article having excellent transparency, scratch resistance, and surface hardness. [Background technology]

[0002] Polycarbonate resins are excellent in mechanical strength, electrical properties, transparency, etc., and are widely used as engineering plastics in various fields such as the electrical and electronic equipment field, the automotive field, etc. In recent years, in these fields, molded products have become thinner, less expensive, smaller, and lighter, and further performance improvements in molding materials are required, and several proposals have been made.

[0003] For example, Patent Document 1 discloses a polycarbonate resin composition that contains 100 parts by mass of a polycarbonate resin (A) having a specific structure and 0.1 to 12 parts by mass of a graft copolymer (B) having a polyethylene polymer as the main chain and a vinyl polymer segment as the side chain. The document also discloses that the polycarbonate resin composition has excellent resistance to scratches caused by fingernails. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2017-110180 A Summary of the Invention [Problem to be solved by the invention]

[0005] It has been known that polycarbonate resins containing structural units derived from bisphenol C tend to have high pencil hardness. Here, a molded product made of a polycarbonate resin containing structural units derived from bisphenol C may be used as a product without being treated with paint or the like (hereinafter, sometimes referred to as "paintless"). However, the present inventors have conducted research and found that such molded products have some problems with fingernail scratch resistance, despite their high pencil hardness. The resin composition described in Patent Document 1 above is a resin composition with excellent fingernail scratch resistance, but the examples in the same document pursue jet blackness and the like. That is, for applications requiring transparency, the development of new materials is required. In addition, in paintless products, fingerprints and the like may be wiped off with a cleaner or the like. Therefore, fingernail scratch resistance after wiping off the solvent is also required. Furthermore, even if the transparency and nail scratch resistance of the resin composition are improved by blending appropriate additives into the polycarbonate resin, the extrudability and transparency may be deteriorated depending on the type of additive. The present invention aims to solve these problems, and to provide a resin composition that has excellent surface hardness and transparency, excellent scratch resistance, and excellent resistance to fingernail scratches both initially and after solvent wiping off, and that has a high rate of transparency retention, particularly after an abrasion test, and excellent extrudability, and a molded article using the resin composition. [Means for solving the problem]

[0006] In view of the above-mentioned problems, the present inventors have conducted research and found that the above-mentioned problems can be solved by blending a triester compound obtained from a specific polycarboxylic acid and a monohydric alcohol, and / or a triester compound obtained from a polyhydric alcohol and a monocarboxylic acid, with a polycarbonate resin. <1> Preferably, <2> ~ <8> Thus, the above problem was solved. <1> (B) a triester compound is contained in an amount of 0.3 to 10.0 parts by mass relative to 100 parts by mass of (A) a polycarbonate resin, The (A) polycarbonate resin contains 5 mol % or more of a structural unit represented by the following formula (1) among all structural units, the triester compound (B) is an ester compound obtained from a polycarboxylic acid and a monohydric alcohol having 20 or more carbon atoms, an ester compound obtained from a polyhydric alcohol and a monohydric carboxylic acid having 20 or more carbon atoms, or a mixture of both of these ester compounds; resin composition; Formula (1) [ka] In formula (1), R 1 represents a methyl group, and R 2 represents a hydrogen atom or a methyl group, and X 1 represents one of the following formulas: [ka] R 3 and R 4 each independently represents a hydrogen atom or a methyl group, and Z represents a group that bonds with C to form an alicyclic hydrocarbon having 6 to 12 carbon atoms which may have a substituent. <2> The (B) triester compound is a triester compound consisting of a trivalent carboxylic acid and a monohydric alcohol having 20 or more carbon atoms, or a triester compound consisting of a trihydric alcohol and a monovalent carboxylic acid having 20 or more carbon atoms, or a mixture thereof. <1> The resin composition according to claim 1. <3> The (A) polycarbonate resin further contains a structural unit represented by the following formula (2): <1> or <2> The resin composition according to claim 1 ; Formula (2) [ka] In formula (2), X 2 represents one of the following formulas: [ka] R 3 and R 4each independently represents a hydrogen atom or a methyl group, and Z represents a group that bonds with C to form an alicyclic hydrocarbon having 6 to 12 carbon atoms which may have a substituent. <4> The (A) polycarbonate resin contains, among all structural units, 5 to 95 mol % of the structural units represented by the formula (1) and 95 to 5 mol % of the structural units represented by the formula (2). <3> The resin composition according to claim 1. <5> When molded into a 2 mm thick molded product, the haze is 5.0% or less. <1> ~ <10> The resin composition according to any one of the preceding claims. <6> <1> ~ <5> A molded article formed from the resin composition according to any one of claims 1 to 5. Effect of the Invention

[0007] The present invention makes it possible to provide a resin composition having high surface hardness, excellent scratch resistance and extrusion properties, high transparency, and excellent resistance to fingernail scratches both initially and after the solvent has been wiped off, and in particular a high rate of retention of transparency after an abrasion test, and a molded article using the resin composition. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0008] The present invention will be described in detail below. In this specification, the word "to" is used to mean that the numerical values ​​before and after it are included as the lower limit and upper limit.

[0009] The resin composition of the present invention is characterized in that it contains 0.3 to 10.0 parts by mass of (B) a triester compound relative to 100 parts by mass of (A) polycarbonate resin, the (A) polycarbonate resin contains 5 mol % or more of a structural unit represented by formula (1) described below among all structural units, and the (B) triester compound is an ester compound obtained from a polycarboxylic acid and a monohydric alcohol having 20 or more carbon atoms, an ester compound obtained from a polyhydric alcohol and a monocarboxylic acid having 20 or more carbon atoms, or a mixture of both of these ester compounds.

[0010] By adopting such a constitution, it is possible to provide a resin composition which has high surface hardness, excellent extrudability, high transparency, and excellent resistance to scratching by a fingernail both initially and after wiping off the solvent.

[0011] <(A) Polycarbonate resin> The polycarbonate resin (A) used in the resin composition of the present invention contains 5 mol % or more of the structural unit represented by formula (1) in all structural units. Formula (1) [ka] In formula (1), R 1 represents a methyl group, and R 2 represents a hydrogen atom or a methyl group, and X 1 represents one of the following formulas: [ka] R 3 and R 4 each independently represents a hydrogen atom or a methyl group, and Z represents a group that bonds with C to form an alicyclic hydrocarbon having 6 to 12 carbon atoms which may have a substituent.

[0012] The two R in Eq. (1) 2 may be the same or different, and are preferably the same. 2 is preferably a hydrogen atom.

[0013] In formula (1), X 1 teeth, [ka] If R 3 and R 4 At least one of the groups is preferably a methyl group, and both of the groups are more preferably methyl groups. Also X 1 but, [ka] In this case, Z is bonded to the carbon C bonded to the two phenyl groups in the above formula (1) to form a divalent alicyclic hydrocarbon group having 6 to 12 carbon atoms. Examples of the divalent alicyclic hydrocarbon group include cycloalkylidene groups such as a cyclohexylidene group, a cycloheptylidene group, a cyclododecylidene group, an adamantylidene group, and a cyclododecylidene group. Substituted groups include those having a methyl or ethyl substituent. Among these, a cyclohexylidene group, a methyl-substituted cyclohexylidene group (preferably a 3,3,5-trimethyl-substituted cyclohexylidene group), and a cyclododecylidene group are preferred. In formula (1), X 1 is preferably the following structure: [ka]

[0014] The polycarbonate resin (A) in the present invention contains the structural unit represented by formula (1) in a content of 5 mol% or more, preferably 10 mol% or more, more preferably 20 mol% or more, even more preferably 40 mol% or more, even more preferably 50 mol% or more, even more preferably 60 mol% or more, and even more preferably 65 mol% or more of the total structural units. The upper limit is not limited, but the content is preferably 95 mol% or less, more preferably 90 mol% or less, even more preferably 85 mol% or less, even more preferably 80 mol% or less, and even more preferably 77 mol% or less of the total structural units. The content of the structural unit represented by formula (1) in the polycarbonate resin (A) may be 40 mol% or less of the total structural units.

[0015] In the present invention, the polycarbonate resin (A) may contain only one type of structural unit represented by formula (1), or may contain two or more types. When two or more types are contained, it is preferable that the total amount thereof is within the above range.

[0016] Specific examples of preferred structural units of the above formula (1) include the following i) to iv). i) A structural unit composed of 2,2-bis(3-methyl-4-hydroxyphenyl)propane, i.e., R 1 is a methyl group, R 2 is a hydrogen atom, X 1 A structural unit in which is -C(CH3)2-, ii) A structural unit composed of 2,2-bis(3,5-dimethyl-4-hydroxyphenyl)propane, i.e., R 1 is a methyl group, R 2 is a methyl group, X 1 A structural unit in which is -C(CH3)2-, iii) A structural unit composed of 2,2-bis(3-methyl-4-hydroxyphenyl)cyclohexane, i.e., R 1 is a methyl group, R 2 is a hydrogen atom, X 1 a structural unit in which iv) A structural unit composed of 2,2-bis(3-methyl-4-hydroxyphenyl)cyclododecane, i.e., R 1 is a methyl group, R 2 is a hydrogen atom, X 1 is a structural unit which is a cyclododecylidene group. Among these, the above i), ii) and iii) are preferred, the above i) and iii) are more preferred, and the above i) is even more preferred.

[0017] In the present invention, the polycarbonate resin (A) may have a structural unit other than the structural unit represented by the above formula (1). As the structural unit, a structural unit represented by the following formula (2) is preferable. Formula (2) [ka] In formula (2), X 2 represents one of the following formulas: [ka] R 3 and R 4each independently represents a hydrogen atom or a methyl group, and Z represents a group that bonds with C to form an alicyclic hydrocarbon having 6 to 12 carbon atoms which may have a substituent. Examples of the alicyclic hydrocarbon formed by bonding Z to C include cycloalkylidene groups such as a cyclohexylidene group, a cycloheptylidene group, a cyclododecylidene group, an adamantylidene group, and a cyclododecylidene group. Examples of the alicyclic hydrocarbon having a substituent formed by bonding Z to C include the methyl- and ethyl-substituted alicyclic hydrocarbon groups described above. Among these, a cyclohexylidene group, a methyl-substituted cyclohexylidene group (preferably a 3,3,5-trimethyl-substituted cyclohexylidene group), and a cyclododecylidene group are preferred.

[0018] X in Equation (2) 2 The preferred range of X in formula (1) is 1 That is, in the formula (2), X 2 is preferably the following structure: [ka] R 3 and R 4 At least one of the groups is preferably a methyl group, and both of the groups are more preferably methyl groups.

[0019] A preferred specific example of the structural unit represented by the above formula (2) is 2,2-bis(4-hydroxyphenyl)propane, that is, a structural unit (carbonate structural unit) constituted by bisphenol-A. In the present invention, the structural unit represented by formula (2) is preferably contained in an amount of 5 mol% or more, more preferably 10 mol% or more, even more preferably 15 mol% or more, even more preferably 20 mol% or more, and even more preferably 23 mol% or more of the total structural units. The structural unit represented by formula (2) may be contained in an amount of 60 mol% or more of the total structural units. The structural unit represented by formula (2) is preferably contained in an amount of 95 mol% or less, more preferably 90 mol% or less, even more preferably 80 mol% or less, even more preferably 60 mol% or less, even more preferably 50 mol% or less, even more preferably 40 mol% or less, and even more preferably 35 mol% or less of the total structural units. In the present invention, the polycarbonate resin (A) may not contain the structural unit represented by formula (2), may contain only one type, or may contain two or more types. When two or more types are contained, it is preferable that the total amount thereof is within the above range.

[0020] In the present invention, the (A) polycarbonate resin may contain, as another structural unit, a structural unit derived from a dihydroxy compound shown below.

[0021] Bis(4-hydroxyphenyl)methane, 2,2-bis(4-hydroxyphenyl)butane, 2,2-bis(4-hydroxyphenyl)pentane, 2,2-bis(4-hydroxyphenyl)-4-methylpentane, 2,2-bis(4-hydroxy-3-methylphenyl)propane, 2,2-bis(4-hydroxy-3,5-dimethylphenyl)propane, 2,2-bis(4-hydroxy-3-(1-methylethyl)phenyl)propane, 2,2-bis(4-hydroxy-3-tert-butylphenyl)propane, 2,2-bis(4-hydroxy-3-(1-methylpropyl)phenyl)propane, 2,2-bis(4-hydroxy-3-cyclohexylphenyl)propane, 2,2-bis(4-hydroxy-3-phenylphenyl)propane, 1,1-bis(4-hydroxyphenyl)decane, 1,1-bis(4-hydroxyphenyl) Cyclohexane, 1,1-bis(4-hydroxyphenyl)-1-phenylethane, 1,1-bis(4-hydroxyphenyl)phenylmethane, 1,1-bis(4-hydroxy-3-methylphenyl)cyclohexane, 1,1-bis(4-hydroxy-3,5-dimethylphenyl)cyclohexane, 1,1-bis(4-hydroxy-3-(1-methylethyl)phenyl)cyclohexane, 1,1-bis(4-hydroxy-3-tert-butylphenyl)cyclohexane, 1,1-bis(4-hydroxy-3-(1-methylpropyl)phenyl)cyclohexane, 1,1-bis(4-hydroxy-3-cyclohexylphenyl)cyclohexane, 1,1-bis(4-hydroxy-3-phenylphenyl)cyclohexane, 1,1-bis(4-hydroxy-3-methylphenyl)-1-phenylethane, 1,1-bis(4-hydroxy-3 ,5-dimethylphenyl)-1-phenylethane, 1,1-bis(4-hydroxy-3-(1-methylethyl)phenyl)-1-phenylethane, 1,1-bis(4-hydroxy-3-tert-butylphenyl)-1-phenylethane, 1,1-bis(4-hydroxy-3-(1-methylpropyl)phenyl)-1-phenylethane, 1,1-bis(4-hydroxy-3-cyclohexylphenyl)-1-phenylethane, 1,1-bis(4-hydroxy-3-phenylphenyl)-1-phenylethane, 1,1-bis(4-hydroxyphenyl)cyclopentane, 1,1-bis(4-hydroxyphenyl)cyclopentane, 1,1-bis(4-hydroxyphenyl)cyclooctane, 4,4'-(1,3-phenylenediisopropylidene)bisphenol, 4,4'-(1,4-phenylenediisopropylidene)bisphenol, 9,9-bis(4-hydroxyphenyl)fluorene, 9,9-bis(4-hydroxy-3-methylphenyl)fluorene, 4,4'-dihydroxybenzophenone, 4,4'-dihydroxyphenyl ether, 4,4'-dihydroxybiphenyl, 1,1-bis(4-hydroxyphenyl)-3,3,5-trimethylcyclohexane, 1,1-bis(4-hydroxy-6-methyl-3-tert-butylphenyl)butane.

[0022] Another example of a structural unit is the structural unit represented by formula (1) described in paragraph 0008 of WO2017 / 099226. Furthermore, the description in paragraphs 0043 to 0052 of WO2017 / 099226 may also be taken into consideration, the contents of which are incorporated herein by reference.

[0023] Furthermore, another embodiment of the other structural unit is also exemplified by a structural unit represented by the following formula (3). [ka] In formula (3), R 15 ~R 18each independently represents a hydrogen atom, a fluorine atom, a chlorine atom, a bromine atom, an iodine atom, an alkyl group having 1 to 9 carbon atoms, an aryl group having 6 to 12 carbon atoms, an alkoxy group having 1 to 5 carbon atoms, an alkenyl group having 2 to 5 carbon atoms, or an aralkyl group having 7 to 17 carbon atoms; n1, n2, and n3 each independently represent an integer of 0 to 4. For details of the structural unit represented by formula (3), reference can be made to the description in JP2011-046769A, the contents of which are incorporated herein by reference.

[0024] In the (A) polycarbonate resin, the content of structural units other than the structural units represented by the above formula (1) and the structural units represented by the formula (2) is preferably 30 mol % or less, more preferably 20 mol % or less, and even more preferably 10 mol % or less, and may be 5 mol % or less, or 1 mol % or less, of all structural units.

[0025] A preferred embodiment of the polycarbonate resin (A) in the present invention will be described below. (1) A polycarbonate resin containing more than 95 mol % of structural units represented by formula (1) among all structural units. (2) A polycarbonate resin containing, among all structural units, 5 to 95 mol % of structural units represented by formula (1) and 95 to 5 mol % or more of structural units other than the structural units represented by formula (1) (preferably structural units represented by formula (2)). When the polycarbonate resin used in the present invention contains a structural unit other than the structural unit represented by formula (1) (preferably a structural unit represented by formula (2)), the following blend forms are exemplified. A mixture of a polycarbonate resin (A1) in which more than 50 mol % (preferably 70 mol % or more, 95 mol % or more) of all structural units are composed of structural units represented by formula (1) and a polycarbonate resin (A2) in which more than 95 mol % of all structural units are composed of structural units represented by formula (2): A copolymer polycarbonate resin (A3) in which the sum of the structural units represented by formula (1) and the structural units represented by formula (2) accounts for more than 95 mol % of all structural units: A mixture of the polycarbonate resin (A1), the polycarbonate resin (A2), and the copolymer polycarbonate resin (A3): a mixture of the polycarbonate resin (A1) and the copolymer polycarbonate resin (A3); a mixture of the copolymer polycarbonate resin (A3) and the polycarbonate resin (A2); In any of the above embodiments, a mixture containing two or more of at least one of the polycarbonate resin (A1), the polycarbonate resin (A2), and the copolymer polycarbonate resin (A3); In any embodiment, it is sufficient that the structural unit represented by formula (1) is contained in the (A) polycarbonate resin in a proportion of 5 mol % or more, and further, it is preferable that the structural unit represented by formula (1) and the structural unit represented by formula (2) are contained in all structural units in a proportion that satisfies the above-mentioned preferable range.

[0026] In the present invention, among the above-mentioned blend forms, a form containing a polycarbonate resin (A1) and a polycarbonate resin (A2) is particularly preferred. When the blend contains a polycarbonate resin (A1) and a polycarbonate resin (A2), the mixing ratio of the two is preferably 5:95 to 95:5 by mass, more preferably 10:90 to 95:5, even more preferably 15:85 to 95:5, even more preferably 15:85 to 90:10, even more preferably 50:50 to 90:10, even more preferably 60:40 to 85:15, even more preferably 65:35 to 85:15, even more particularly preferably 60:40 to 80:20, and may be 70:30 to 80:20. The resin composition of the present invention may contain only one kind of the (A1) polycarbonate resin and the (A2) polycarbonate resin, or may contain two or more kinds. When two or more kinds are contained, it is preferable that the total amount is within the above range. By adopting such a constitution, the pencil hardness can be increased.

[0027] In the present invention, the lower limit of the viscosity average molecular weight (Mv) of the (A) polycarbonate resin is preferably 9,000 or more, more preferably 10,000 or more, and even more preferably 12,000 or more. The upper limit of Mv is preferably 32,000 or less, more preferably 30,000 or less, and even more preferably 28,000 or less. By setting the viscosity average molecular weight to the above lower limit or more, moldability is improved and molded articles having high mechanical strength can be obtained, while by setting the viscosity average molecular weight to the above upper limit or less, the flowability of the molded article is improved and thin-walled molded articles can be efficiently produced. The viscosity average molecular weight (Mv) is measured according to the method described in the examples below (hereinafter, the same applies to Mv). When two or more (A) polycarbonate resins are contained, the viscosity average molecular weight is the sum of the values ​​obtained by multiplying the viscosity average molecular weight of each polycarbonate resin by the mass fraction. Hereinafter, the same applies to the viscosity average molecular weight.

[0028] The polycarbonate resin (A) has a pencil hardness of 3B to 2H, preferably B to 2H, and more preferably HB to 2H, as measured according to ISO 15184. The pencil hardness is measured according to the method described in the examples below (hereinafter the same applies to pencil hardness). When two or more types of polycarbonate resins (A) are contained, the pencil hardness of the mixture is preferably within the above range.

[0029] The method for producing the polycarbonate resin (A) is not particularly limited, and any known method can be adopted.Examples thereof include interfacial polymerization method, melt transesterification method, pyridine method, ring-opening polymerization method of cyclic carbonate compound, and solid-phase transesterification method of prepolymer.Among these, interfacial polymerization method and melt transesterification method are preferred.

[0030] The resin composition of the present invention preferably contains the polycarbonate resin (A) in a proportion of 80 mass% or more of the composition, more preferably 85 mass% or more, even more preferably 90 mass% or more, and even more preferably 93 mass% or more. The upper limit of the polycarbonate resin (A) is not particularly specified, but can be, for example, 99.4 mass% or less. The resin composition of the present invention may contain only one type of (A) polycarbonate resin, or may contain two or more types. When two or more types are contained, the total amount is preferably within the above range.

[0031] <(B) Triester Compound> The resin composition of the present invention contains (B) a triester compound. The triester compound (B) used in the present invention is an ester compound obtained from a polycarboxylic acid and a monohydric alcohol having 20 or more carbon atoms (preferably 20 to 50 carbon atoms), an ester compound obtained from a polyhydric alcohol and a monocarboxylic acid having 20 or more carbon atoms (preferably 20 to 50 carbon atoms), or a mixture of both. The resin composition of the present invention contains such a triester compound, which suppresses decomposition of the polycarbonate resin, effectively suppresses gas generation during molding, and has excellent compatibility with the polycarbonate resin, and therefore can provide a resin composition capable of forming a molded product having excellent extrudability, high transparency, and excellent initial and after-solvent-wiping resistance to fingernail scratches.

[0032] The (B) triester compound is preferably a triester compound formed from a trivalent carboxylic acid and a monohydric alcohol, a triester compound formed from a monovalent carboxylic acid and a trihydric alcohol, or a mixture thereof. The monohydric alcohol and the monocarboxylic acid may each contain at least one of an aliphatic structure, an alicyclic structure, and an aromatic structure, and preferably contain an aliphatic structure and / or an alicyclic structure. The monohydric alcohol and the monocarboxylic acid are preferably each composed of a linear or branched aliphatic structure or an alicyclic structure, and a carboxyl group or a hydroxyl group. The monohydric alcohol and the monocarboxylic acid each have 20 or more carbon atoms, and preferably 21 or more carbon atoms. The upper limit of the carbon number is preferably 50 or less, more preferably 40 or less, even more preferably 32 or less, and still more preferably 30 or less. The trivalent carboxylic acid and the trihydric alcohol may each contain at least one of an aliphatic structure, an alicyclic structure, and an aromatic structure, and preferably each contains an aliphatic structure and / or an alicyclic structure. The trivalent carboxylic acid and the trihydric alcohol each preferably have a linear or branched aliphatic structure or alicyclic structure and a carboxyl group or a hydroxyl group. The number of carbon atoms in the trivalent carboxylic acid and the trihydric alcohol each preferably is 3 or more. The number of carbon atoms in the trivalent carboxylic acid and the trihydric alcohol each preferably is 10 or less, more preferably 8 or less.

[0033] In particular, the triester compound used in the present invention is preferably a triester compound obtained from a trivalent carboxylic acid having 3 to 10 carbon atoms and a monohydric alcohol having 20 to 40 carbon atoms, a triester compound obtained from a trihydric alcohol having 3 to 10 carbon atoms and a monovalent carboxylic acid having 20 to 40 carbon atoms, or a mixture of two or more of them, more preferably a triester compound obtained from a trivalent carboxylic acid having 3 to 10 carbon atoms and a monohydric alcohol having 20 to 30 carbon atoms, a triester compound obtained from a trihydric alcohol having 3 to 10 carbon atoms and a monovalent carboxylic acid having 20 to 30 carbon atoms, or a mixture of two or more of them, and even more preferably a triester compound obtained from a trihydric alcohol having 3 to 10 carbon atoms and a monovalent carboxylic acid having 20 to 30 carbon atoms, or a mixture of two or more of them. Furthermore, in the triester compound composed of a trihydric alcohol and a monocarboxylic acid used in the present invention, the number of carbon atoms in the monocarboxylic acid is preferably 10 or more, more preferably 10 to 20, larger than the number of carbon atoms in the trihydric alcohol. By adopting such a constitution, gas is less likely to be generated during extrusion or molding, and the appearance and physical properties of the molded product tend to be further improved.

[0034] Specific examples of monocarboxylic acids having 20 or more carbon atoms (the number in parentheses is the number of carbon atoms) include behenic acid (22), lignoceric acid (24), cerotic acid (26), montanic acid (28), and melissic acid (30).

[0035] Specific examples of monohydric alcohols having 20 or more carbon atoms (the number of carbon atoms is in parentheses) include behenyl alcohol (22) and montanyl alcohol (28).

[0036] Specific examples of trivalent carboxylic acids (number of carbon atoms in parentheses) include tricarballylic acid (6), 1,2,3-benzenetricarboxylic acid (9), 1,3,5-benzenetricarboxylic acid (9), 1,2,4-benzenetricarboxylic acid (9), 5-methyl-1,2,4-benzenetricarboxylic acid (10), 1,2,3-cyclohexanetricarboxylic acid (9), 1,3,5-cyclohexanetricarboxylic acid (9), and 1,2,4-cyclohexanetricarboxylic acid (9).

[0037] Specific examples of trihydric alcohols (number of carbon atoms in parentheses) include glycerin (3), trimethylolpropane (6), trimethylolethane (5), triethylolethane (8), 1,2,4-butanetriol (4), hydroxyquinol (6), phloroglucinol (6), pyroganol (6), and 1,2,4-cyclohexanetriol (6).

[0038] The hydroxyl value of the (B) triester compound is preferably 100 mgKOH / g or less, more preferably 70 mgKOH / g or less, even more preferably 50 mgKOH / g or less, and even more preferably 10 mgKOH / g or less. The lower limit of the hydroxyl value of the (B) triester compound is not particularly specified, but is, for example, 1 mgKOH / g or more. By making the hydroxyl value of the (B) triester compound 100 mgKOH / g or less, the promotion of decomposition of the polycarbonate resin is effectively suppressed, gas is less likely to be generated during extrusion or molding, and the appearance and physical properties of the molded product tend to be improved, which is preferable. According to this embodiment, the molded article obtained from the composition of the present invention also has excellent resistance to scratches caused by fingernails after wiping with cotton soaked in ethanol.

[0039] The molecular weight of the (B) triester compound used in the present invention is preferably not more than 2000, more preferably not more than 1800, and even more preferably not more than 1400. The lower limit is preferably not less than 1000. When the molecular weight of the (B) triester compound is within the above range, a molded product having an excellent balance between high transparency and high resistance to fingernail scratches can be obtained.

[0040] The triester compound used in the present invention is often a mixture of multiple compounds having different carbon numbers, but in the present invention, it refers to an ester compound contained as a main component (preferably 50% by mass or more, more preferably 70% by mass or more).

[0041] The resin composition of the present invention contains 0.3 to 10.0 parts by mass of (B) triester compound relative to 100 parts by mass of (A) polycarbonate resin. The lower limit of the blending amount of (B) triester compound is preferably 0.4 parts by mass or more, more preferably 0.5 parts by mass or more, even more preferably 0.6 parts by mass or more, even more preferably 0.8 parts by mass or more, even more preferably 1.0 parts by mass or more, even more preferably 1.5 parts by mass or more, particularly more preferably 1.8 parts by mass or more, and may even be 2.0 parts by mass or more, more than 2.0 parts by mass, or 2.2 parts by mass or more relative to 100 parts by mass of (A) polycarbonate resin. By setting it in the above range, the nail scratch resistance can be further improved. The upper limit of the blending amount of the (B) triester compound is preferably 9.0 parts by mass or less, and may be 8.0 parts by mass or less, 7.0 parts by mass or less, 6.0 parts by mass or less, 5.0 parts by mass or less, 4.0 parts by mass or less, 3.0 parts by mass or less, or 2.5 parts by mass or less, relative to 100 parts by mass of the (A) polycarbonate resin. By setting it within the preferred range, hydrolysis resistance is improved and mold contamination can be more effectively suppressed. In the present invention, even if the blending amount of the (B) triester compound is small, it is possible to obtain a configuration that has excellent fingernail scratch resistance. The resin composition of the present invention may contain only one type of (B) triester compound, or may contain two or more types. When two or more types are contained, the total amount is preferably within the above range.

[0042] <Other ingredients> The resin composition of the present invention may contain other components as necessary, as long as the desired physical properties are not significantly impaired. Examples of other components include thermoplastic resins other than the polycarbonate resins described above (e.g., acrylic resins, etc.), various resin additives, etc. The resin composition of the present invention preferably does not contain an inorganic filler, but may contain an inorganic filler. By containing an inorganic filler, the mechanical strength of the obtained molded article can be further improved. As an embodiment of the resin composition of the present invention, a resin composition that does not contain an inorganic filler or contains an inorganic filler at a ratio of 8 parts by mass or less (preferably 6 parts by mass or less, more preferably 4 parts by mass or less, and even more preferably 1 part by mass or less) relative to 100 parts by mass of the (A) polycarbonate resin is exemplified. By not containing an inorganic filler or setting the blending amount within the above range, the transparency of the obtained molded article can be further improved. For the inorganic filler, the description in paragraphs 0075 to 0079 of JP 2017-110180 A can be referred to, and the contents thereof are incorporated herein. Examples of resin additives include stabilizers (heat stabilizers, antioxidants, etc.), UV absorbers, antistatic agents, flame retardants, flame retardant assistants, dyes, pigments, antifogging agents, lubricants, antiblocking agents, flow improvers, plasticizers, dispersants, antibacterial agents, etc. The resin additives may be contained alone or in any combination and ratio of two or more kinds. The resin composition of the present invention may be configured to be substantially free of any other release agent than the triester compound (B). Substantially free means that the amount of the other release agent is less than 0.5 parts by mass, preferably 0.3 parts by mass or less, more preferably 0.1 parts by mass or less, even more preferably 0.01 parts by mass or less, even more preferably 0.001 parts by mass or less, and even more preferably 0.0001 parts by mass or less, per 100 parts by mass of the polycarbonate resin (A).

[0043] <<Acrylic resin>> The polycarbonate resin composition of the present invention may contain an acrylic resin as a thermoplastic resin other than the polycarbonate resin. The acrylic resin is preferably an acrylic resin having a structural unit represented by the following formula (X). Formula (X) [ka] In formula (X), R 6 , R 7 and R 8 each independently represents a hydrogen atom or a hydrocarbon group having 1 to 20 carbon atoms; R 9 represents an aromatic hydrocarbon group having 6 to 20 carbon atoms which may have a substituent, or an aliphatic hydrocarbon group having 1 to 3 carbon atoms which is substituted with an aromatic hydrocarbon group having 6 to 17 carbon atoms which may have a substituent.

[0044] In addition to the above, the acrylic resin used in the present invention may be one described in WO2014 / 038500, WO2013 / 094898, JP2006-199774A, and JP2010-116501A, the contents of which are incorporated herein by reference. When an acrylic resin is blended, the blending amount is preferably in the range of 1 to 30% by mass, and more preferably in the range of 1 to 10% by mass, of the polycarbonate resin composition of the present invention.

[0045] <<Stabilizer>> The stabilizers include heat stabilizers and antioxidants. As the heat stabilizer, a phosphorus-based stabilizer is preferably used. Any known phosphorus stabilizer can be used. Specific examples include phosphorus oxoacids such as phosphoric acid, phosphonic acid, phosphorous acid, phosphinic acid, and polyphosphoric acid; metal acid pyrophosphates such as sodium acid pyrophosphate, potassium acid pyrophosphate, and calcium acid pyrophosphate; phosphates of Group 1 or Group 2B metals such as potassium phosphate, sodium phosphate, cesium phosphate, and zinc phosphate; organic phosphate compounds, organic phosphite compounds, and organic phosphonite compounds, with organic phosphite compounds being particularly preferred.

[0046] Examples of organic phosphite compounds include triphenyl phosphite, tris(mononylphenyl)phosphite, tris(mononyl / dinonyl phenyl)phosphite, tris(2,4-di-tert-butylphenyl)phosphite, monooctyl diphenyl phosphite, dioctyl monophenyl phosphite, monodecyl diphenyl phosphite, didecyl monophenyl phosphite, tridecyl phosphite, trilauryl phosphite, tristearyl phosphite, and 2,2-methylenebis(4,6-di-tert-butylphenyl)octyl phosphite. Specific examples of such organic phosphite compounds include "ADK STAB (registered trademark; the same applies below) 1178," "ADK STAB 2112," and "ADK STAB HP-10" manufactured by ADEKA Corporation, "JP-351," "JP-360," and "JP-3CP" manufactured by Johoku Chemical Industry Co., Ltd., and "IRGAFOS (registered trademark; the same applies below) 168" manufactured by BASF.

[0047] As the antioxidant, a hindered phenol-based stabilizer is preferably used. Specific examples of hindered phenol stabilizers include pentaerythritol tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], octadecyl-3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, thiodiethylene bis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], N,N'-hexane-1,6-diylbis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionamide], 2,4-dimethyl-6-(1-methylpentadecyl)phenol, diethyl[[3,5-bis(1,1-dimethylethyl)-4-hydroxyphenyl]methyl]phosphate, 3,3',3'',5,5',5''-hexa-tert-butyl-a,a',a''-(mesityle) 4,6-bis(octylthiomethyl)-o-cresol, ethylene bis(oxyethylene) bis[3-(5-tert-butyl-4-hydroxy-m-tolyl)propionate], hexamethylene bis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], 1,3,5-tris(3,5-di-tert-butyl -4-hydroxybenzyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, 2,6-di-tert-butyl-4-(4,6-bis(octylthio)-1,3,5-triazin-2-ylamino)phenol, 2-[1-(2-hydroxy-3,5-di-tert-pentylphenyl)ethyl]-4,6-di-tert-pentylphenyl acrylate, and the like.

[0048] Among them, pentaerythritol tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] and octadecyl-3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate are preferred. Specific examples of such hindered phenol stabilizers include "Irganox (registered trademark, the same applies below) 1010" and "Irganox 1076" manufactured by BASF, and "Adeka STAB AO-50" and "Adeka STAB AO-60" manufactured by ADEKA.

[0049] The content of the stabilizer in the resin composition of the present invention is usually 0.001 parts by mass or more, preferably 0.005 parts by mass or more, more preferably 0.01 parts by mass or more, and usually 1 part by mass or less, preferably 0.5 parts by mass or less, more preferably 0.3 parts by mass or less, relative to 100 parts by mass of the polycarbonate resin. By setting the content of the stabilizer within the above range, the effect of adding the stabilizer is more effectively exhibited.

[0050] <<Ultraviolet absorber>> For information on ultraviolet absorbents, refer to paragraphs 0059 to 0062 of JP2016-216534A, the contents of which are incorporated herein by reference.

[0051] <<Antistatic agent>> For information on the antistatic agent, refer to paragraphs 0063 to 0067 of JP2016-216534A, the contents of which are incorporated herein by reference.

[0052] <<Flame retardants>> For flame retardants, refer to paragraphs 0068 to 0075 of JP2016-216534A, the contents of which are incorporated herein by reference.

[0053] <Characteristics of resin composition> The resin composition of the present invention can achieve low haze. For example, the haze of a molded product of the resin composition of the present invention molded to a thickness of 2 mm can be set to 5.0% or less, and can also be set to 3.0% or less, 2.0% or less, 1.0% or less, 0.5% or less, or 0.4% or less. The ideal lower limit of the haze is 0%, but a haze of 0.01% or more, or even 0.07% or more is also practical. The method for measuring the haze is as described in the examples below.

[0054] A 2 mm thick test piece (preferably a test piece having a length of 150 mm x width of 100 mm x thickness of 2 mm) formed from the resin composition of the present invention has a Δ haze, which is the difference in haze before and after an initial reciprocating abrasion test using bleached cotton (100% cotton, 20 x 20 count), of preferably 5.00% or less, more preferably 4.50% or less, even more preferably 4.00 or less, even more preferably 3.50% or less, even more preferably 3.00% or less, and even more preferably 2.00% or less. The lower limit of Δ haze before and after the initial reciprocating abrasion test is ideally 0%, but 0.01% or more, or even 0.07% or more is also practical. The method for measuring Δ haze before and after the initial reciprocating abrasion test is as described in the examples below.

[0055] The difference between the Δ haze value before and after the reciprocating abrasion test after the solvent is wiped off and the Δ haze value before and after the initial reciprocating abrasion test of a 2 mm thick test piece (preferably a test piece having a length of 150 mm x width of 100 mm x thickness of 2 mm) formed from the resin composition of the present invention (Δ haze before and after the reciprocating abrasion test after the solvent is wiped off - Δ haze before and after the initial reciprocating abrasion test) is preferably 2.0 or less, more preferably 1.5 or less, even more preferably 1.2 or less, even more preferably 1.0 or less, and even more preferably 0.9 or less. The lower limit of the Δ haze before and after the reciprocating abrasion test after the solvent is wiped off - Δ haze before and after the initial reciprocating abrasion test is ideally 0%, but even 0.01% or more, or even 0.07% or more is a practical level. The Δ haze before and after the reciprocal abrasion test after the solvent was wiped off - the Δ haze before and after the initial reciprocal abrasion test are as described in the Examples section below.

[0056] <Method of producing resin composition> There is no limitation on the method for producing the resin composition of the present invention, and a wide variety of known methods for producing polycarbonate resin compositions can be used. Examples of such methods include a method in which the polycarbonate resin and triester compound, as well as other components to be blended as necessary, are premixed using various mixers such as a tumbler or a Henschel mixer, and then melt-kneaded using a mixer such as a Banbury mixer, a roll, a Brabender, a single-screw kneading extruder, a twin-screw kneading extruder, or a kneader. The melt-kneading temperature is not particularly limited, but is usually in the range of 240 to 320°C.

[0057] <Molded products> The above-mentioned resin composition (for example, pellets) can be molded into a molded article by various molding methods. That is, the molded article of the present invention is molded from the resin composition of the present invention. The shape of the molded article is not particularly limited and can be appropriately selected depending on the use and purpose of the molded article, and examples thereof include film-like, rod-like, cylindrical, annular, circular, elliptical, polygonal, irregularly shaped, hollow, frame-like, box-like, panel-like, button-like, etc. Among these, film-like, frame-like, panel-like, and button-like shapes are preferred, and the thickness is, for example, about 1 mm to 5 mm in the case of the frame-like and panel-like shapes.

[0058] The method for forming the molded article is not particularly limited, and a conventionally known molding method can be adopted, for example, injection molding, injection compression molding, extrusion molding, profile extrusion, transfer molding, hollow molding, gas-assisted hollow molding, blow molding, extrusion blow molding, IMC (in-mold coating molding) molding, rotational molding, multi-layer molding, two-color molding, insert molding, sandwich molding, foam molding, pressure molding, etc. In particular, the resin composition of the present invention is suitable for molded articles obtained by injection molding, injection compression molding, and extrusion molding. However, it goes without saying that the resin composition of the present invention is not limited to molded articles obtained by these methods.

[0059] The molded article of the present invention is suitable for use in parts of electric and electronic devices, office automation equipment, mobile information terminals, machine parts, home appliances, vehicle parts, various containers, lighting equipment, etc. Among these, it is particularly suitable for use in housings of electric and electronic devices, office automation equipment, information terminal devices, and home appliances, lighting equipment, and vehicle parts (particularly vehicle interior parts), and is particularly suitable for use in vehicle interior parts. EXAMPLES

[0060] The present invention will be described in more detail below with reference to examples. The materials, amounts, ratios, processing contents, processing procedures, etc. shown in the following examples can be appropriately changed without departing from the spirit of the present invention. Therefore, the scope of the present invention is not limited to the specific examples shown below.

[0061] 1. Raw materials <Production Example 1: Production of Polycarbonate Resin A1> 26.14 mol (6.75 kg) of bisphenol C (BPC) and 26.79 mol (5.74 kg) of diphenyl carbonate were placed in a stainless steel reactor (internal volume: 10 L) equipped with a stirrer and a distillate condenser. The inside of the reactor was replaced with nitrogen gas, and the temperature was raised to 220°C in a nitrogen gas atmosphere over 30 minutes. Next, the reaction liquid in the reactor was stirred, and cesium carbonate (Cs2CO3) was added as a transesterification catalyst to the molten reaction liquid at a ratio of 1.5 × 10 -6 The reaction solution was stirred and fermented in a nitrogen gas atmosphere at 220° C. for 30 minutes. Next, the pressure in the reactor was reduced to 100 Torr over 40 minutes at the same temperature, and the reaction was continued for another 100 minutes to distill off phenol. Next, the temperature in the reactor was raised to 284°C over 60 minutes, and the pressure was reduced to 3 Torr, and phenol equivalent to almost the entire theoretical amount was distilled out. Next, the pressure in the reactor was kept below 1 Torr at the same temperature, and the reaction was continued for another 60 minutes to complete the polycondensation reaction. At this time, the stirring speed of the stirrer was 38 rpm, the temperature of the reaction liquid immediately before the end of the reaction was 289°C, and the stirring power was 1.00 kW. Next, the reaction liquid in the molten state was fed into a twin-screw extruder, and p-toluenesulfonate in an amount four times by mole relative to the cesium carbonate was fed from the first feed port of the twin-screw extruder and kneaded with the reaction liquid. Thereafter, the reaction liquid was extruded into strands through the die of the twin-screw extruder and cut with a cutter to obtain pellets of polycarbonate resin A1.

[0062] <Production Example 2: Synthesis of tribehenyl trimellitate> Trimethyl trimellitate (Tokyo Chemical Industry Co., Ltd., 32.0 g), behenyl alcohol (Tokyo Chemical Industry Co., Ltd., 124 g) and tetrabutyl orthotitanate (Tokyo Chemical Industry Co., Ltd.) in 5% by mass toluene solution (2.40 mL) were mixed and reacted at 220°C for 3 hours under a nitrogen atmosphere, then reduced to 6 kPa and heated at 220°C for 2 hours, while distilling off the methanol produced. After the reaction, the mixture was diluted with toluene (280 mL) and washed with a 1% by mass aqueous solution (140 g) of disodium hydrogen citrate (FUJIFILM Wako Pure Chemical Co., Ltd.) 1.5-hydrate, and then washed twice with water (140 g). The obtained oil layer was filtered through Celite to remove residual insoluble matter, and the solvent was distilled off under reduced pressure. A solution of chloroform (140 mL) and toluene (140 mL) was added to the residue to effect recrystallization, and the remaining solvent was then distilled off under reduced pressure to obtain tribehenyl trimellitate (103 g) as a white powder.

[0063] The materials shown in Table 1 below were used to produce the resin composition of the present invention. [Table 1]

[0064] <Measurement of viscosity average molecular weight (Mv) of polycarbonate resin> The viscosity average molecular weight (Mv) of the polycarbonate resin was calculated from the intrinsic viscosity (η) (unit: dL / g) at 20°C using an Ubbelohde viscometer with methylene chloride as a solvent, and the viscosity average molecular weight (Mv) was calculated from the following Schnell viscosity formula. η = 1.23 × 10 -4 Mv 0.83

[0065] <Measurement of pencil hardness of polycarbonate resin> The polycarbonate resin pellets were dried at 100°C for 5 hours, and then a flat test piece (150mm x 100mm x 2mm thick) was produced using an injection molding machine ("α-2000i-150B" manufactured by FANUC CORPORATION) under the conditions of a cylinder set temperature of 260°C, a mold temperature of 70°C, a screw rotation speed of 100 rpm, and an injection speed of 30 mm / sec. The pencil hardness of this flat test piece was measured at a load of 750g using a pencil hardness tester in accordance with ISO 15184. The pencil hardness tester used was a product of Toyo Seiki Seisakusho Co., Ltd.

[0066] <Measurement of hydroxyl value of triester compounds and their substitutes> The hydroxyl value is the number of milligrams of potassium hydroxide required to neutralize the acetic acid bonded to the hydroxyl groups when 1 g of a sample is acetylated, and is an index that indicates the number of hydroxyl groups that remain unreacted when the alcohol, which is the raw material for an ester compound, is esterified with a carboxylic acid compound. The hydroxyl value was measured according to the method specified in JIS K 0070.

[0067] 2. Examples 1 to 7, Comparative Examples 1 to 17 <Production of Resin Composition Pellets> The components shown in Table 1 above were blended in the proportions shown in Table 2 or Table 3 below (all parts by weight), and mixed uniformly in a tumbler mixer. The mixture was then fed into the extruder from the barrel upstream of the extruder using a twin-screw extruder (TEX30α manufactured by The Japan Steel Works, Ltd.) with a cylinder set temperature of 260°C, a screw rotation speed of 180 rpm, and a discharge rate of 30 kg / hr, and melt-kneaded to obtain resin composition pellets (however, extrusion was not possible for Comparative Example 11).

[0068] <Molar ratio of polycarbonate resin> The molar ratios (mol %) in Tables 2 and 3 described later are indicators showing the content of the structural unit represented by formula (1) in the polycarbonate resin contained in the resin composition, and were calculated from the viscosity average molecular weight using the mixing ratio of the resins used and the molecular weight of the structural unit represented by formula (1).

[0069] <Extrusion possibility> In the production of the resin composition pellets, whether or not extrusion was possible was visually confirmed, and evaluated as follows. A: Extrusion possible b: Extrusion instability c: Cannot be extruded (polycarbonate resin decomposes)

[0070] <Extrusion gas generation amount> In the production of the above resin composition pellets, the amount of gas generated in Comparative Example 2 was set as the standard, and the amount of gas generated that was equal to or less than that was evaluated as standard gas generation (a). The amount of gas generated by extrusion compared with the standard amount was visually evaluated as follows. a: Standard gas generation rate b: Somewhat C: Many

[0071] <Overall evaluation of extrusion> Based on the results of the above-mentioned extrusion feasibility and the amount of gas generated, the samples were evaluated as follows. A: Both the ability to extrude and the amount of gas generated are a. B: Other than A above and C below. C: At least one of the ability to extrude and the amount of gas generated is c.

[0072] <Production of evaluation test pieces as molded bodies> The resin composition pellets obtained above were dried at 100°C for 5 hours, and then injection-molded into flat test pieces measuring 150 mm x 100 mm x 2 mm in thickness using an injection molding machine ("α-2000i-150B" manufactured by Fanuc Corporation) under conditions of a cylinder setting temperature of 260°C, a mold temperature of 70°C, a screw rotation speed of 100 rpm, and an injection speed of 30 mm / sec. In the table, "unmoldable" means that extrusion was impossible or extremely unstable, so that a test piece for evaluation could not be molded.

[0073] <Measurement of pencil hardness of resin composition> The pencil hardness of the flat test piece obtained above was determined by measuring with a pencil hardness tester under a load of 1 kg in accordance with ISO 15184. The pencil hardness tester used was a product of Toyo Seiki Seisakusho Co., Ltd.

[0074] <Haze measurement> The haze (unit: %) of the flat test piece obtained above was measured using a haze meter. The haze meter used was a NDH-2000 type haze meter manufactured by Nippon Denshoku Industries Co., Ltd.

[0075] <Dynamic friction coefficient (30N)> The flat test piece obtained above was scanned with a 1 mmφ spherical terminal at a test speed of 100 mm / sec over a test distance of 100 mm while varying the vertical load from 1 N to 50 N using a scratch tester in accordance with ISO 19252. The horizontal and vertical loads were measured at a point where the load was 30 N, and the dynamic friction coefficient (horizontal load / vertical load) was calculated. A smaller dynamic friction coefficient is preferable. The scratch tester used was a product of Kato Tech Co., Ltd.

[0076] <Resistance to nail scratches (initial stage)> The flat test piece produced above was rubbed with a fingernail 10 times to perform a sensory evaluation. A: It doesn't scratch and has good slip resistance. b: It scratches a little, but it slides well. c: Less damage than d, but still damage. d: Hurt.

[0077] <Resistance to fingernail scratches after wiping off solvent> The surface of the flat test piece produced above was wiped with cotton soaked in ethanol, and a sensory evaluation was carried out in the same manner as in the above-mentioned fingernail scratch resistance.

[0078] <Δ haze before and after initial reciprocating abrasion test> The haze of the flat test piece obtained above was measured in the same manner as above (the haze measured here was designated as haze a). On the other hand, a similar flat test piece obtained above was folded 18 times (100% cotton, 20×20 count bleach cut to 15cm×33cm) and attached to the jig of the flat test piece, and tested at 40 reciprocating cycles / min, 1kg load, and 500 reciprocating cycles. After the reciprocating abrasion test, the flat test piece was measured for haze in the same manner as above (the haze at this time was designated as haze b). "Haze b - haze a" was designated as Δ haze before and after the reciprocating abrasion test. The flat surface abrasion tester used was manufactured by Daiei Scientific Instruments and Systems. The bleach used was made by Nankai Co., Ltd.

[0079] <Δ haze before and after reciprocating abrasion test after wiping off the solvent - Δ haze before and after initial reciprocating abrasion test> The surface of the flat test piece obtained above was wiped with gauze soaked in ethanol, and the haze was measured in the same manner as above (the haze measured at this time was designated as haze c). Next, in the same manner as above, a flat abrasion tester was used, and a piece of bleached cloth (100% cotton, 20×20 count bleached cloth cut to 15 cm×33 cm) was folded 18 times, attached to the jig of the flat abrasion tester, and tested at a reciprocating cycle of 40 times / min, a load of 1 kg, and 500 reciprocating cycles. After the reciprocating abrasion test, the haze of the flat test piece was measured in the same manner as above (the haze at this time was designated as haze d). "Haze d - haze c - Δ haze before and after initial reciprocating abrasion test" was designated as "Δ haze before and after reciprocating abrasion test after wiping off the solvent - Δ haze before and after initial reciprocating abrasion test". The flat surface abrasion tester used was manufactured by Daiei Scientific Instruments and Systems. The bleach used was made by Nankai Co., Ltd.

[0080] <Overall evaluation (extrusion, haze, and fingernail scratch resistance)> The evaluation was made comprehensively based on extrusion property, haze, and fingernail scratch resistance. 1: Overall extrudability rating is A, haze is 5.0% or less, and fingernail scratch resistance (initial) and fingernail scratch resistance after solvent wiping are a. 2: Other than 1 above and 3 below. 3: One or more of the following are met: The overall extrusion rating is C. Haze is greater than 5.0%. Fingernail scratch resistance is c or d. Resistance to fingernail scratches after wiping off the solvent is c or d.

[0081] The results are shown in Tables 2 and 3 below.

[0082] [Table 2]

[0083] [Table 3]

[0084] In the above table, "proportion of formula (1)" refers to the proportion (mol %) of the structural unit represented by formula (1) among all the structural units constituting the polycarbonate resin. As is clear from the above results, the resin composition of the present invention had high surface hardness, excellent extrudability, low haze, and excellent initial and after-solvent wiping resistance (Examples 1 to 7). Furthermore, the difference between the Δ haze before and after the initial reciprocating abrasion test and the Δ haze before and after the reciprocating abrasion test after the solvent wiping and the Δ haze before and after the initial reciprocating abrasion test also tended to be small. In contrast, when the structural unit represented by formula (1) was not included (Comparative Example 1 and Comparative Examples 15 to 17), any of the above performances were poor. Specifically, the initial and after solvent wiping resistance was poor, the haze was high, the extrudability was poor, and the Δhaze before and after the initial reciprocating abrasion test was high. In addition, when only ester compounds other than the triester compounds defined in the claims of the present invention and their substitutes (B3 to B8 and B10 above) were blended (Comparative Examples 1 to 12, 16 and 17), the extrudability tended to be poor, the haze was high, and the scratch resistance at the initial stage and after the solvent was wiped off tended to be poor. Furthermore, even if the triester compound defined in the claims of the present invention was contained, when the blending amount was outside the range of the present invention (Comparative Examples 13 and 14), the initial fingernail scratch resistance and the extrudability after wiping off the solvent were poor.

Claims

1. (A) containing 0.3 to 10.0 parts by mass of a triester compound (B) relative to 100 parts by mass of a polycarbonate resin, The polycarbonate resin (A) contains 5 mol % or more of a structural unit represented by the following formula (1) among all structural units, The resin composition according to claim 1, wherein the triester compound (B) is an ester compound obtained from a polycarboxylic acid and a monohydric alcohol having 21 or more carbon atoms, an ester compound obtained from a polyhydric alcohol and a monohydric carboxylic acid having 21 or more carbon atoms, or a mixture of both of these ester compounds, The resin composition contains the polycarbonate resin (A) in a proportion of 80% by mass or more, the triester compound (B) is a triester compound composed of a trivalent carboxylic acid and a monohydric alcohol having 21 or more carbon atoms, or a triester compound composed of a trihydric alcohol and a monovalent carboxylic acid having 21 or more carbon atoms, or a mixture thereof; resin composition; Formula (1) 【Chemistry 1】 In formula (1), R 1 represents a methyl group, R 2 represents a hydrogen atom or a methyl group, X 1 represents one of the following formulas: 【Chemistry 2】 R 3 and R 4 each independently represents a hydrogen atom or a methyl group, and Z represents a group that bonds with C to form an alicyclic hydrocarbon having 6 to 12 carbon atoms which may have a substituent.

2. The resin composition according to claim 1, wherein the polycarbonate resin (A) further contains a structural unit represented by the following formula (2): Formula (2) 【Chemistry 3】 In formula (2), X 2 represents one of the following formulas: 【Chemistry 4】 R 3 and R 4 each independently represents a hydrogen atom or a methyl group, and Z represents a group that bonds with C to form an alicyclic hydrocarbon having 6 to 12 carbon atoms which may have a substituent.

3. The polycarbonate resin (A) contains, among all structural units, 5 to 95 mol % of the structural unit represented by the formula (1) and 95 to 5 mol % of the structural unit represented by the formula (2). The resin composition according to claim 2.

4. The resin composition according to any one of claims 1 to 3, which has a haze of 5.0% or less when molded into a molded product having a thickness of 2 mm.

5. A molded article formed from the resin composition according to any one of claims 1 to 4.

Citation Information

Patent Citations

  • Aromatic polycarbonate resin composition

    JP1997176473A

  • Polycarbonate resin composition and molded article

    JP2017110180A